AN EVALUATION REPORT ON OMS 786 IN RICE FIELDS - A. Naghib Hazrati; E. Javadian (Tehran University of Medical Sciences, 1972)
Regarding the importance of rice fields, as the main mosquito breeding places, use of chemical larvicides has been under consideration in Malaria Eradication Programs. In this trial, OMS 786 was used, to study the method and cost of application of this larvicide in the rice fields. Two form of larvicides (1% sand granule, and 50% E.C.) were used in four formulations. (10 and 15 kg. of 1% S.G./hectar, 100 and 150 ml. of 50% E.C./hectar).The density of Anopheline and Culex larvae were checked before application, and also in specific intervals after application, in different plots, and were compared with control. The results of the trial shows, that OMS 786 (especially in E.C. form) can successfully be used in the rice fie1ds to eliminate the mosquito activities in the problem areas. The trial also shows that the cost of operation (especially for 50% E.C.) is less than other methods.